2017
DOI: 10.1016/j.apcatb.2016.10.063
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced photocatalytic degradation of methylene blue and methyl orange by ZnO:Eu nanoparticles

Abstract: ZnO nanoparticles doped with different Eu 3+ percentages were synthesized in water (ZnO:Eu(x%)-W) and other solvents (methanol ZnO:Eu(x%)-M and ethanol ZnO:Eu(x%)-E). X-ray diffraction (XRD), transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS), optical absorption and photoluminescence (PL) spectroscopy were used for characterization of the nanoparticles. Our results showed influence of europium doping and solvents on size, particles agglomeration, light absorption and photocatalytic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
103
2
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 346 publications
(114 citation statements)
references
References 99 publications
8
103
2
1
Order By: Relevance
“…They confirmed higher MB removal compared to MO. They also confirmed the significant effect of the presence of OH groups during the removal of MB, while for MO, the most important factor was the formation of holes (Trandafilović et al 2017). Beura and Thangadurai studied the degradation efficiency of the Sn-ZnO-graphene for mixed dyes (MO and MB).…”
Section: Effect Of Type Of Dye On Photocatalytic Performancementioning
confidence: 55%
“…They confirmed higher MB removal compared to MO. They also confirmed the significant effect of the presence of OH groups during the removal of MB, while for MO, the most important factor was the formation of holes (Trandafilović et al 2017). Beura and Thangadurai studied the degradation efficiency of the Sn-ZnO-graphene for mixed dyes (MO and MB).…”
Section: Effect Of Type Of Dye On Photocatalytic Performancementioning
confidence: 55%
“…Metal oxide nanoparticles (NPs) such as titanium dioxide (TiO 2 ) [18,27], zinc oxide (ZnO) [28], nickel oxide (NiO) [29], cerium dioxide (CeO 2 ) [30], copper oxide (CuO) [30,31], and manganese oxides (MnO x ) [32] have been widely studied in oxidation processes. Among those, MnO x NPs have attracted special attention for the removal of organic dyes due to their unique structure and physicochemical properties [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…Before irradiation, the Eu 52 Ni 56− x Cd x /CdS‐3 gave an intense signal at 1.922, which was attributed to the paramagnetic defect of CdS (Figure a) . An EPR signal with g of 2.003 was observed upon 30 min of irradiation, which is assigned to the paramagnetic Eu 2+ species . These results revealed that the photoinduced electron of CdS can transfer from conduction‐band of CdS to Eu 3+ , resulting in reduced Eu 2+ (Figure a).…”
Section: Methodsmentioning
confidence: 90%